An Extended Model of the Theory of Planned Behavior: An Empirical Study of Entrepreneurial Intention and Entrepreneurial Behavior in College Students - Lihua, Duan (Frontiers in Psychology, 2022)
Based on the literature review, we adopted the theory of planned behavior as the theoretical framework introduced entrepreneurial situational factors and entrepreneurial execution intention, and constructed a two-step extended entrepreneurial intention – behavior model. The structural equation was constructed using AMOS24.0 to empirically analyze the antecedent variables of college students' entrepreneurial intention and the influencing factors of entrepreneurial behavior. The empirical results showed that expected material possessions, expected social reputation, expected self-evaluation, mission and responsibility, and career development are the antecedent variables of entrepreneurial attitude. Support from families and friends, college’s views, and the role models are antecedent variables of entrepreneurial subjective norms. Professional ability, entrepreneurial ability, entrepreneurial experiences, and personality traits are the antecedent variables of entrepreneurial perceived behavior control. Attitude, subjective norms, perceived behavior control, entrepreneurial situational factors, and entrepreneurial execution intention have significant impacts on the formation of college students’ entrepreneurial intention, while entrepreneurial intention, perceived behavior control, entrepreneurial situational factors, and implementation intention have significant impacts on the transition to actual entrepreneurial actions.